C-Lobe of Lactoferrin: The Whole Story of the Half-Molecule - Sujata Sharma; Mau Sinha; Sanket Kaushik; Punit Kaur; Tej P. Singh (Biochemistry Research International)
Lactoferrin is an iron-binding diferric glycoprotein present in most of the exocrine secretions. The major role of lactoferrin, which is found abundantly in colostrum, is antimicrobial action for the defense of mammary gland and the neonates. Lactoferrin consists of two equal halves, designated as N-lobe and C-lobe, each of which contains one iron-binding site. While the N-lobe of lactoferrin has been extensively studied and is known for its enhanced antimicrobial effect, the C-lobe of lactoferrin mediates various therapeutic functions which are still being discovered. The potential of the C-lobe in the treatment of gastropathy, diabetes, and corneal wounds and injuries has been indicated. This review provides the details of the proteolytic preparation of C-lobe, and interspecies comparisons of its sequence and structure, as well as the scope of its therapeutic applications.